Sudden Cardiac Death as the First Clinical Manifestation in Infants With Asymptomatic Ventricular Pre-excitation: Two Case Reports and Review of the Literature - Moises Rodriguez-Gonzalez; Miguel Matamala-Morillo; Ana Castellano-Martinez (Mazandaran University of Medical Sciences, 2019)
Introduction: The real risk of Sudden Cardiac Death (SCD) in Asymptomatic Wolff-Parkinson-White (AWPW) syndrome is still unclear, and the literature is controversial about the best management strategy. Usually, SCD has been reported as the first event in asymptomatic or undiagnosed infants with AWPWs. So adequate risk stratification is warranted to prevent the occurrence of life-threatening arrhythmias in these patients. However, none of the available diagnostic tests is satisfactory to predict SCD. Case Presentation: We report two cases of AWPW syndrome in infants that experienced SCD as their first clinical manifestation. Conclusion: AWPW syndrome in infants is not rare. It is also a challenging condition that implies a very weak but real risk of SCD, which is very difficult to ascertain with current diagnostic methods. In this article, we review the literature about these cases and discuss the adequate management of these patients.